Stage of lactation, parity, breed, milk composition, and minerals affect the nonenzymatic antioxidant activity of sheep milk - Giorgia Stocco; Claudio Cipolat-Gotet; Stefano Biffani; Michela Ablondi; Alessio Negro; Andrea Summer; Panagiota Kyriakaki; Alexandros Mavrommatis; Eleni Tsiplakou (Journal of Dairy Science)
ABSTRACT: The aims of this study were to (1) characterize sheep milk for nonenzymatic antioxidant activity via 2 different assays, namely the ferric reducing antioxidant power (FRAP) and the 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH), and (2) investigate the effect of milk composition and animal-related parameters on these 2 assays by using the generalized additive mixed model (GAMM) approach. A total of 740 ewes belonging to the Massese and Comisana breeds were sampled once during the morning milking across 11 sampling sessions. All milk samples were analyzed for fat, protein, CN, and lactose, SCS, and minerals (Ca, Mg, Na, and Cl). The FRAP and DPPH assays were tested to measure the nonenzymatic antioxidant activity of milk, expressed as micromolar equivalents (μM Eq) of ascorbic acid/mL of milk and percent of inhibition, respectively. The GAMM model included the effect of parity and breed as parametric terms, and the effect of DIM, milk yield, and the interactions protein × fat, CN × SCS, Ca × Mg, and Na × Cl as smooth terms. The sampling day was included in the model as a random effect. Results revealed that the nonenzymatic antioxidant capacity of sheep milk, expressed as FRAP, was affected by DIM, potentially because of changes in milk composition over time. Conversely, parity and breed of ewes affected DPPH, suggesting that age- and breed-specific factors are related to specific components in milk acting as hydrogen donors. Milk fat and high CN percentages were found to significantly affect FRAP, and protein content was crucial for high DPPH levels. Additionally, Ca and Mg emerged as important nonenzymatic antioxidants for both FRAP and DPPH, highlighting their important role in antioxidant activity of sheep milk. In contrast, combinations of Na and Cl were particularly influential for FRAP, revealing the complex relationship between these minerals and nonenzymatic antioxidant activity of milk. These findings offer valuable insights into the factors affecting the antioxidative properties of sheep milk, highlighting the need for further exploration of other nonenzymatic antioxidants and their contribution to the total antioxidant activity.